2019
DOI: 10.1016/j.earscirev.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Establishing tephrostratigraphic frameworks to aid the study of abrupt climatic and glacial transitions: a case study of the Last Glacial-Interglacial Transition in the British Isles (c. 16-8 ka BP)

Abstract: Establishing tephrostratigraphic frameworks to aid the study of abrupt climatic and glacial transitions: a case study of the Last Glacial-Interglacial Transition in the British Isles (c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 185 publications
2
32
0
Order By: Relevance
“…The most consistent and best developed tephra layer occurs within l.u.5a, the geochemical results for which, and the laboratory procedures adopted, are provided in Appendices C, D and B.4. A total alkali versus silica (TAS) plot ( Figure 7A) indicates these glass shards to be rhyolitic in composition and when compared with documented tephras from N. Europe dating to between 16 and 8 ka (Timms et al, 2019), to align closely with the distinctive Askja-S Tephra. Biplots of major oxides, most notably of CaO-FeO ( Figure 7B) and K 2 O-TiO 2 (7C), support this affiliation.…”
Section: Contradictory Proposals For the Timing Of The Demise Of The mentioning
confidence: 72%
See 1 more Smart Citation
“…The most consistent and best developed tephra layer occurs within l.u.5a, the geochemical results for which, and the laboratory procedures adopted, are provided in Appendices C, D and B.4. A total alkali versus silica (TAS) plot ( Figure 7A) indicates these glass shards to be rhyolitic in composition and when compared with documented tephras from N. Europe dating to between 16 and 8 ka (Timms et al, 2019), to align closely with the distinctive Askja-S Tephra. Biplots of major oxides, most notably of CaO-FeO ( Figure 7B) and K 2 O-TiO 2 (7C), support this affiliation.…”
Section: Contradictory Proposals For the Timing Of The Demise Of The mentioning
confidence: 72%
“…An older date of 11.23 ± 226 cal 14 C ka BP has been suggested for this tephra based on evidence from a site in Poland(Ott et al 2016), but this is an outlier compared with the majority of dates available(Kearney et al 2018). For completeness, however, both age estimates are employed in separate age models presented in Appendix F. older tephra in the Kingshouse 2 sequence, assigned to the Abernethy Tephra (AT), is more equivocal, because of its close chemical similarity with the Vedde Ash (VA), which dates to ~12.1 ka BP (Bronk Ramsey et al, 2015): it has been argued that small traces of glass shards that have been assigned to the AT could be reworked VA instead (seeTimms et al, 2019). This is unlikely in this case, however, because the VA is usually the most prominent peak in glass shard concentrations in Lateglacial deposits in sites in the Scottish Highlands, and if present in the Kingshouse 2 basin, it should be more strongly represented.…”
mentioning
confidence: 99%
“…This framework is primarily based on (crypto)tephra layers from Icelandic volcanic centres (e.g. Wastegård and Davies, 2009; Lawson et al ., 2012; Plunkett and Pilcher, 2018; Wastegård et al ., 2018; Timms et al ., 2019). However, recent studies have demonstrated that a considerable number of previously unknown cryptotephras identified in this region for the Holocene and Late Glacial in fact originate from non‐Icelandic sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have demonstrated that a considerable number of previously unknown cryptotephras identified in this region for the Holocene and Late Glacial in fact originate from non‐Icelandic sources (e.g. North America and the North Pacific region; Plunkett and Pilcher, 2018; Timms et al ., 2019). This yields the possibility of hemisphere‐wide synchronisations of different archives based on cryptotephra isochrons.…”
Section: Introductionmentioning
confidence: 99%
“…This finding lends support to the identification of the Aniakchak tephra in south Wales and is consistent with other examples of transatlantic transport of ash. The White River Ash eastern lobe, originating from Mount Churchill (Alaska), is found in a number of northern European sites including as far east as Poland (Jensen et al, 2014;Watson et al, 2017a), while traces of tephras originating from the Cascades (northwest America), have also been discovered at Finglas River, southwest Ireland, (Turney, 1998;Timms et al, 2019).…”
Section: Aniakchak Cfe II (Llo09_297)mentioning
confidence: 99%